E-LEARNING SEBAGAI MEDIA PEMBELAJARAN PESERTA DIDIK - Hamidah, Wanda; Putri, Rully; Hartanto, Wiwin (Universitas Tanjungpura, 2022)
Learning media is a very important aspect in the learning process. The media is to support the teacher to convey material to students. The teacher's task is to choose the right learning media to improve students' understanding. E-learning is a learning model that is made in digital format through electronic devices. This article discusses e-learning as a learning medium for students. The purpose of writing this article is to determine the use of e-learning in a learning system. expand access to education for students, so that learning modules or materials can be easily accessed without being limited by space and time, effective and interactive for students. This e-learning-based application contains estimates and general descriptions, plans for learning activities that utilize computer networks and the internet. The scope of this learning plan includes 4 main components, namely, teaching materials or materials, objectives, teaching and learning processes and also evaluation.